RAQAMLI PLATFORMALARDA TA’LIM RESURSLARINI MOSLAShTIRISh VA TA’LIM SIFATIGA TA’SIRI - Nurmaxanov, K.E. (SCIENCE and SOCIETY, 2025)
This article analyzes the processes of adapting educational resources on digital platforms, their integration into the learning process, and their impact on the quality of education. Adapted resources contribute to the effective organization of learning and the improvement of educational outcomes. Additionally, the article highlights the advantages of using digital technologies, practical recommendations, and promising development directions.